Antenna with artificial magnetic conductor for wireless application - Rahim, MKA; Hamid, MR; Samsuri, NA; Murad, NA; Zubir, F; Ayop, O; Yusof, MFM; Majid, HA (2019)
— This paper discussed the recent works on Artificial Magnetic Conductor (AMC) with the antenna. Two different application for antenna with AMC have been discussed. The first application is the antenna with AMC that has been used for RFID system to detect the metal object. Without incorporating AMC with antenna the system cannot be detected. When the AMC is attached with the RFID Tag antenna the system is back to normal where longer distance is achieved. The second application is used for flexible AMC using textile material for signal transmission enhancement. Using two antennas for on body application the system has been tested using AMC and without AMC. It shows that the transmission is better when there is an AMC attach to the body compared without AMC. Index Terms — Artificial Magnetic Conductor, high impedance surface, metamaterial, reflection phase,